Selenium as an inorganic biostimulant in onion grown in a semi-arid climate - Laíza G. de Paiva; Leilson C. Grangeiro; Clístenes W. A. do Nascimento; Romualdo M. C. Costa; Natali A. E. Pereira; Renner B. de Lima; Bruna de P. Souza; Luiz H. de A. Carmo; Renata R. T. Oliveira; Éric G. Morais (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The common climatic characteristics in semi-arid regions can cause abiotic stress and be a limiting factor for crops. Under these conditions, the use of beneficial elements such as selenium (Se) is an alternative to mitigate the harmful effects of abiotic stresses and increase yield. Therefore, this research aimed to evaluate the agronomic performance of onion grown in a semi-arid region under the application of Se. A field experiment was performed in a randomized block design, where five doses of Se (0, 15, 30, 45, and 60 g ha-1), by foliar application, were tested on two onion hybrids (Andrômeda and Rio das Antas). Growth, nutritional and yield variables were analyzed. Se increased the height and accumulation of dry mass in onion plants, with a maximum at the 60 g ha-1 dose of Se, the same dose at which the highest commercial (78.15 t ha-1) and total (86.03 t ha-1) bulb yields were obtained in Rio das Antas; however, for Andrômeda, there was no effect of Se on yield. Applied Se doses also increased the content of this element in the bulbs. Despite increasing bulb yields only in the Rio das Antas hybrid, 60 g ha-1 of Se is recommended for onions due to its effects on plant growth and the biofortification of bulbs with Se.